A Measure in Which Boolean Negation is Exponentially Powerful - Skyum, Sven (DAIMI Report Series, 1982)
The power of negation in combinatorial complexity theory has for a long time been an intriguing question. In this paper we demonstrate that in the more restricted setting of projections among families of Boolean functions, negation can be exponentially powerful.